2015
DOI: 10.1016/j.medengphy.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

On growth measurements of abdominal aortic aneurysms using maximally inscribed spheres

Abstract: The maximum diameter, total volume of the abdominal aorta, and its growth rate are usually regarded as key factors for making a decision on the therapeutic operation time for an abdominal aortic aneurysm (AAA) patient. There is, however, a debate on what is the best standard method to measure the diameter. Currently, two dominant methods for measuring the maximum diameter are used. One is measured on the planes perpendicular to the aneurism's central line (orthogonal diameter) and the other one is measured on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 36 publications
0
46
0
Order By: Relevance
“…For the maximum diameter calculation, the method of inscribed spheres 19 , which consist of calculating diameters of maximally inscribed spheres along the centerline, was used. Therefore, the largest value of the diameter along the centerline was defined as the maximum diameter.…”
Section: Methodsmentioning
confidence: 99%
“…For the maximum diameter calculation, the method of inscribed spheres 19 , which consist of calculating diameters of maximally inscribed spheres along the centerline, was used. Therefore, the largest value of the diameter along the centerline was defined as the maximum diameter.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 12(b) shows the computed range of maximum diameter's rate compared with that of the clinical data analysis performed in Ref. [47]. Watton et al [25] were the first to study the effects of the spine (as a rigid plane) in an idealized model of evolving aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…The longitudinal CT data from 14 patients are used in Ref. [47]. Table 2 The average amount (calculated over the whole AAA surface) of von Mises stress VMS, longitudinal stretch k 1 , circumferential stretch k 2 , collagen content per reference area M c , collagen content per current area m c , smooth muscle content per reference area M m , and smooth muscle content per current area m m .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Doyle et al [4] used CFD and longitudinal CT data (from four time points) to show ILT development and expansion in AAA. In addition, Zambrano et al [33] reported in a study from patients longitudinal CT studies that ILT accumulation rate would relate in a linear manner with the AAA expansion rate. They calculated these rates by measuring the changes in volume between two consecutive CT scans of ILT and AAA, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These rates were defined as the changes of volumes between two consecutive scans over that time interval. Each color refers to longitudinal CT data of a different patient [33]. (c) The changes of active proteolytic enzymes in the ILT's depth.…”
Section: Methodsmentioning
confidence: 99%